Current paranoid thinking in patients with delusions: the presence of cognitive-affective biases. - Freeman, D; Dunn, G; Fowler, D; Bebbington, P; Kuipers, E; Emsley, R; Jolley, S; Garety, P (Oxford University Press, 2013)
BACKGROUND: There has been renewed interest in the influence of affect on psychosis. Psychological research on persecutory delusions ascribes a prominent role to cognitive processes related to negative affect: anxiety leads to the anticipation of threat within paranoia; depressive negative ideas about the self create a sense of vulnerability in which paranoid thoughts flourish; and self-consciousness enhances feelings of the self as a target. The objective of this study was to examine such affective processes in relation to state paranoia in patients with delusions. METHODS: 130 patients with delusions in the context of a nonaffective psychosis diagnosis (predominately schizophrenia) were assessed for contemporaneous levels of persecutory ideation on 5 visual analog scales. Measures were taken of anxiety, depression, threat anticipation, interpretation of ambiguity, self-focus, and negative ideas about the self. RESULTS: Of the patients, 85% report paranoid thinking at testing. Symptoms of anxiety and depression were highly prevalent. Current paranoid thinking was associated with anxiety, depression, greater anticipation of threat events, negative interpretations of ambiguous events, a self-focused cognitive style, and negative ideas about the self. CONCLUSIONS: The study provides a clear demonstration that a range of emotion-related cognitive biases, each of which could plausibly maintain delusions, are associated with current paranoid thinking in patients with psychosis. We identified biases both in the contents of cognition and in the processing of information. Links between affect and psychosis are central to the understanding of schizophrenia. We conclude that treatment of emotional dysfunction should lead to reductions in current psychotic experiences.